Industry relationships are associated with performing a greater number of sinus balloon dilation procedures. Issue 9 (30th June 2017) - Eloy, Jean Anderson; Svider, Peter F.; Bobian, Michael; Harvey, Richard J.; Gray, Stacey T.; Baredes, Soly; Folbe, Adam J.
Abstract : Background: Industry outreach promotes awareness of novel technologies. However, concerns have been raised that such relationships may also unduly impact medical decision‐making. Our objective in this study was to evaluate industry relationships among practitioners who frequently employ balloon dilation (BD), characterizing whether there is any association between financial relationships and BD utilization. Methods: Provider utilization data (FY‐2014) was accessed for individuals billing BD procedures to Medicare, the largest healthcare payor in the United States. The names of individuals included in these data sets were cross‐referenced with the Centers for Medicare and Medicaid Services Open Payment site to determine the extent of industry relationships during this same year. Individuals included in this analysis were organized by those with "significant" (1, 000 to 10, 000) and "major" (> 10, 000) industry relationships. Practice setting, training, and experience were also evaluated. Results: Of the 302 otolaryngologists who billed enough BDs for inclusion in this data set, 99.3% were in private practice, 89.7% were board‐certified, 8.3% had facial plastic and reconstructive fellowship training, and 1.3% had rhinology fellowship training. There was a significant increase in BDs performed with increasing BD company financial contributions (analysis of variance, p = 0.0003). Individuals without "significant" relationships with BD companies billed fewer BDs than those with at least "significant" (>1, 000) relationships (57.0 ± 4.3 vs 87.7 ± 10.0, p = 0.001). Conclusion: There is an association between receiving money from industry and the frequency with which otolaryngologists employ BD. Although our analysis demonstrates an association, these results in no way imply causation. Further analysis exploring the reasons for this association may be necessary.